1992
DOI: 10.1016/0092-8674(92)90306-w
|View full text |Cite
|
Sign up to set email alerts
|

The small GTPase rab5 functions as a regulatory factor in the early endocytic pathway

Abstract: We have investigated the in vivo functional role of rab5, a small GTPase associated with the plasma membrane and early endosomes. Wild-type rab5 or rab5-ile133, a mutant protein defective in GTP binding, was overexpressed in baby hamster kidney cells. In cells expressing the rab5ile 133 protein, the rate of endocytosis was decreased by 50% compared with normal, while the rate of recycling was not significantly affected. The morphology of early endosomes was also drastically changed by the mutant protein, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

73
909
4
8

Year Published

1996
1996
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,282 publications
(994 citation statements)
references
References 60 publications
73
909
4
8
Order By: Relevance
“…A recent study also suggests the involvement of Rab5 in vesicle budding from the plasma membrane [37]. As a result, overexpression of Rab5 in cultured cells stimulates both receptor-mediated and fluid-phase endocytosis [23,24]. In the present study, we have shown that the GTPhydrolysis-defective Pro$!…”
Section: Figure 4 Molecular Modelling Of An Arg 13 Substitution (Equisupporting
confidence: 65%
See 2 more Smart Citations
“…A recent study also suggests the involvement of Rab5 in vesicle budding from the plasma membrane [37]. As a result, overexpression of Rab5 in cultured cells stimulates both receptor-mediated and fluid-phase endocytosis [23,24]. In the present study, we have shown that the GTPhydrolysis-defective Pro$!…”
Section: Figure 4 Molecular Modelling Of An Arg 13 Substitution (Equisupporting
confidence: 65%
“…The biological function of Rab5 is to regulate endocytosis by promoting early endosome fusion [31,35,36], and possibly vesicle budding at the plasma membrane [37]. As a result, overexpression of Rab5 in cultured cells increased the endocytic activity by 2-fold, as determined by HRP uptake [23,24]. This stimulation of HRP uptake was used as a biological measure of Rab5 activity.…”
Section: Figure 2 Single-step Gtp Hydrolysis By the Gst Fusion Proteimentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is further strengthened by our demonstration that the distribution of rab5 is markedly changed on sucrose gradients. We have shown that in control cells, rab5, a marker for early endosomes [34,41], exhibits a similar distribution to GLUT4 following sucrose-density-gradient analysis of intracellular membranes (Figure 8). However, after ablation, rab5 but not GLUT4 shifts into a more dense region of the gradient.…”
Section: Okadaic Acid On Deglc Transport and Glut4 Ablation In 3t3-l1mentioning
confidence: 73%
“…We have moreover made MDCK cell lines stably expressing a dominant negative mutant of Rab5 or transiently expressing Rab GDI, and have shown that the Rho and Rab families coordinately regulate cell adhesion and migration (Imamura et al, 1998). The Rab small G protein family is implicated in intracellular vesicle tra cking and Rab5 is involved in endocytosis (Bucci et al, 1992;Stenmark et al, 1994;for review, see Novick and Zerial, 1997). Rab GDI is a general regulator of all the Rab family members (for reviews, see Takai et al, 1996;Novick and Zerial;.…”
Section: Introductionmentioning
confidence: 99%